Understanding immigrants’ adherence to child health surveillance services in Portugal?: Highlights from a grounded theory - Mourão, S. (2022)
: Immigrant children are a vulnerable group regarding health. Evidence suggests lower rates of their adherence to health services (vs non-immigrants, Javier et al, 2009), in general, and child health surveillance services (CHSS), in particular. Although the promotion of immigrant children’s adherence to CHSS may be an important step in promoting their health, little is known about the determinants of their (caregivers’) behavior. Objectives: This study aimed to develop a Grounded Theory (GT) on the determinants of adherence to CHSS, of Cape Verdean and Brazilian immigrant child caregivers in Portugal. Methods: 5 Focus Groups (n = 19) and 17 in-depth interviews were conducted, with Cape Verdean, Brazilian and Portuguese child caregivers, from heterogeneous socioeconomic conditions. Data was analyzed using the GT methodology of Strauss and Corbin (1990). Results: Adherence to CHSS is a nuclear and multidimensional concept with several determinants at different levels of analysis. Some of these main determinants are: immigrants’ socioeconomic conditions; (lack of)support for children’s care in the host country; (cultural)beliefs about recommended interventions; the degree of similarity between consults/health-care providers of origin and host countries; (cultural)differences between caregivers’ and health-care providers’ practices. Conclusions: These findings may contribute to incresase the knowledge about immigrants’ (non)adherence behaviors, especially those that aim at health promotion. Also, our À ndings may point to important direction for further research and intervention aiming at the improvement of immigrants’ adherence to CHSS in Portugal.